How are schools implementing a universal social–emotional learning program? Macro- and school-level factors associated with implementation approach - Thierry, Karen L.; Page, Amanda; Currie, Cailin; Posamentier, Jordan; Liu, Yangyang; Choi, Jane; Randall, Haleigh; Rajanbabu, Poojashree; Kim, Tia E.; Widen, Sherri C. (Frontiers in Education, 2022)
For universal SEL programs to contribute to positive learning environments, all school staff must be involved in implementing the program (CASEL, 2020). The current study examined school/district- and macro-level factors associated with two approaches to SEL program implementation observed in schools: (1) classroom teachers as instructors of SEL lessons (i.e., teacher-facilitated) or (2) school counselors as instructors of SEL lessons (i.e., counselor-facilitated). Public elementary and middle schools in the U.S. (N = 6,657), that adopted the Second Step digital program in the 2021-22 school year, were identified as utilizing teacher- or counselor-facilitated implementation using usage records. The results of a Generalized Linear Mixed Model analysis indicated that schools in states with support for SEL (i.e., plans to utilize federal funding for SEL programs or access to systemic SEL consultation) were more likely to use teacher-facilitated implementation than schools without support (OR = 1.64, p < .01, CI = 1.15 – 2.34). Schools in states that were early adopters of stand-alone K-12 SEL standards/competencies tended to be more were nearly two times as likely asthan those without K-12 SEL standards/competencies to use teacher-facilitated implementation (OR = 1.701.95, p = .06< .001, CI = 1.00 – 2.951.53 – 2.48). A qualitative study with Second Step staff who support hundreds of schools utilizing counselor-facilitated implementation identified other potential factors motivating counselors as facilitators, including low SEL buy-in and limited staff capacity. Although this approach has challenges, it could be a pathway to teacher-facilitated implementation over time. Taken together, findings indicate promising strategies for the promotion of more schoolwide use of SEL programs.